ANALISIS ASUPAN ZAT GIZI MAKRO DAN INSIDEN PENYAKIT JANTUNG KORONER PADA PENDUDUK USIA 25-44 TAHUN DI BOGOR (STUDIKOHOR PTM BALITBANGKES 2011-2014) - Lia Nur Uyun; Leni Sri Rahayu (UHAMKA PRESS, 2017)
Coronary heart disease (CHD) is the number one cause of death from non-communicable diseases(NCD), both in Indonesia and in the world. CHD has several risk factors, including food intakewhich is not good. This study was to analyze the food intake on the incidence of CHD in menand women aged 25-44 years in Bogor. This study was a prospective cohort study using a cohortstudy data NCD of Agency for Health Research and Development Ministry of Health of theRepublic of Indonesia. Sampling with purposive sampling technique. Analysis of the data in thisstudy is the univariate analysis. Number of respondents were 1587 subjects. The study foundthe incidence of CHD of 1,20%, the incidence of CHD in men of 1,14% and more affected byCHD are women (1,22%). Most of CHD patients aged 40-44 years old. Protein intake of men15,4% and fat intake of women 31,1%.